Ambientes interativos: a relação entre jogos e design para a interação - Marcela Alves de Almeida (2014)
Digital technology has been weaving itself into the everyday life, creating information and communication networks overlapped with space that are not subordinated to the limits of the buildings. This new reality has challenged the architects to deal with these new layers of information. For this research, architecture mediates social relationships and thus the referrals of the relationship between digital technology and architecture are led by means of the paradigm of interaction. Moreover, it refuses the technological determinism and advocates of actor-network theory in which objects have agency, as well as human beings, giving technology an active role in social construction and vice versa. The subjects under study are the interactive environments and the thesis aims to investigate the conditions for a meaningful dialogue and interaction of people with the space and of people with one another through space. The relationship with games starts by means of the evidence that their structures are present in the constitution of interactive environments. This appropriation of the structures of games for different rational systems is called ludification. From the understanding that interactive environments systems are based on the rational structure of games, the hypothesis of this thesis is that the movement from formal to informal that happens in rational systems is a means to achieve a dialogic interaction. Several interactive environments are analyzed and discussed from categories of spatiality and interactivity, and then the conditions for the design of environments destined to interaction and meaningful relationships are pointed out. Finally, it is argued how the paradigm of interaction that, by placing the emphasis on the lived space, helps overcoming the paradigm of representation that has dominated architecture since the fifteenth century and which still exists in most of architecture practice, theory and critique.